2017
DOI: 10.1007/s11936-017-0523-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Aortic Syndromes: Update in Current Medical Management

Abstract: Advances in medical therapy and non-surgical percutaneous options to manage the specter of acute aortic syndromes have improved both patient morbidity and mortality. There are key features in the patient history and initial exam which physicians should be attuned to in order to diagnose acute aortic syndromes such as aortic dissection, penetrating aortic ulcer, and intramural hematoma. Once recognized, early initiation of the appropriate pharmacologic therapy is important, and further appreciating the limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
8
0
7
Order By: Relevance
“…Development of an intramural hematoma within the wall of the aorta constitutes a true acute aortic syndrome with treatment similar to ruptured AAAs with published data showing anticoagulants are detrimental and may precipitate IHM in this clinical scenario. 82,83 Conversely, other studies have shown enzymes such as MMP-9 are inhibited by FXa antagonists, low-molecular-weight heparin, and vitamin K antagonist use and may promote sac integrity surrounding a stent in a type II endoleak. 80,84 Nonocclusive mural thrombus and aortic wall stability…”
Section: Nonocclusive Trilayered Iltmentioning
confidence: 99%
“…Development of an intramural hematoma within the wall of the aorta constitutes a true acute aortic syndrome with treatment similar to ruptured AAAs with published data showing anticoagulants are detrimental and may precipitate IHM in this clinical scenario. 82,83 Conversely, other studies have shown enzymes such as MMP-9 are inhibited by FXa antagonists, low-molecular-weight heparin, and vitamin K antagonist use and may promote sac integrity surrounding a stent in a type II endoleak. 80,84 Nonocclusive mural thrombus and aortic wall stability…”
Section: Nonocclusive Trilayered Iltmentioning
confidence: 99%
“…Type A affects ascending aorta and arch and may result in occlusion of coronary vessels, incompetence of aortic valve or rupture into the pericardial space. Type A AAS (AD, IMH, and PAU) and aortic emergencies carry a high risk of mortality with conservative management and are treated with emergent surgical intervention (1,5,(18)(19)(20). Type B abnormalities commence distal to the origin of the left subclavian artery and uncomplicated type B ADs can be managed by a more conservative approach with medication and/or EVAR, due to a significantly higher mortality after open repair (1,4,21,22).…”
Section: Prognostication and Triage In Aas And Aortic Emergenciesmentioning
confidence: 99%
“…Type A AAS (AD, IMH, and PAU) and aortic emergencies carry a high risk of mortality with conservative management and are treated with emergent surgical intervention (1,5,(18)(19)(20). Type B abnormalities commence distal to the origin of the left subclavian artery and uncomplicated type B ADs can be managed by a more conservative approach with medication and/or EVAR, due to a significantly higher mortality after open repair (1,4,21,22). Complicated type B dissections with organ or limb malperfusion, progressive dissection, intractable pain, or uncontrolled hypertension are managed by a more invasive approach, preferably EVAR (5).…”
Section: Prognostication and Triage In Aas And Aortic Emergenciesmentioning
confidence: 99%
See 2 more Smart Citations